Classification of Individual Finger Movements Using Intracortical Recordings in Human Motor Cortex. Issue 4 (6th March 2020) - Jorge, Ahmed; Royston, Dylan A; Tyler-Kabara, Elizabeth C; Boninger, Michael L; Collinger, Jennifer L
Abstract: BACKGROUND: Intracortical microelectrode arrays have enabled people with tetraplegia to use a brain–computer interface for reaching and grasping. In order to restore dexterous movements, it will be necessary to control individual fingers. OBJECTIVE: To predict which finger a participant with hand paralysis was attempting to move using intracortical data recorded from the motor cortex. METHODS: A 31-yr-old man with a C5/6 ASIA B spinal cord injury was implanted with 2 88-channel microelectrode arrays in left motor cortex. Across 3 d, the participant observed a virtual hand flex in each finger while neural firing rates were recorded. A 6-class linear discriminant analysis (LDA) classifier, with 10 × 10-fold cross-validation, was used to predict which finger movement was being performed (flexion/extension of all 5 digits and adduction/abduction of the thumb). RESULTS: The mean overall classification accuracy was 67% (range: 65%-76%, chance: 17%), which occurred at an average of 560 ms (range: 420-780 ms) after movement onset. Individually, thumb flexion and thumb adduction were classified with the highest accuracies at 92% and 93%, respectively. The index, middle, ring, and little achieved an accuracy of 65%, 59%, 43%, and 56%, respectively, and, when incorrectly classified, were typically marked as an adjacent finger. The classification accuracies were reflected in a low-dimensional projection of the neural data into LDA space, where the thumb-related movements were most separable from the finger movements. CONCLUSION: Classification of intention to move individual fingers was accurately predicted by intracortical recordings from a human participant with the thumb being particularly independent.